Groups in music : strategies from music therapy - Pavlicevic, Mercedes (Jessica Kingsley Publishers, 2003)
Music therapist Mercédès Pavlicevic develops a broad-based discourse to describe, analyse and guide the practice of group musicking, drawing on her own extensive experience. The text is illustrated with vignettes drawn from a range of formal and informal settings. If you're involved in any kind of group musicking, this book is for you.